The role of public relations practitioners in the Egyptian university hospitals in managing the stages of the Corona virus pandemic crisis" – An applied study in the Greater Cairo region/ Arab Republic of Egypt – - Hassan, Mona AbdelAziz Zakaria (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the role of public relations practitioners in Egyptian university hospitals in managing the phases of the Coronavirus pandemic crisis in the year (2020) AD, through an analytical descriptive study using an interview list, with all the items of the research sample in Egyptian university hospitals, in the Greater Cairo Region (Cairo, Giza, Qalyubia), in which the quarantine was carried out during the Corona virus crisis, and the research concluded that there were no specific tasks to confront the Corona Covid crisis, although practitioners of public relations activities had the ability to deal with the repercussions of the crisis in all stages of management The Coronavirus crisis started from the stage of prediction and discovery to the stage of learning and gaining experiences, avoiding mistakes in the future. The most prominent social media activities for the study sample were (condolences and condolences to the families of doctors, nurses, and the paramedic staff, who died in connection with infection with the Coronavirus while performing their duties). Public relations practitioners for the activity of organizing training courses for doctors, and the agency assisting them in cooperation with the Department of Epidemiology and Surveillance and the Preventive Medicine Sector, regarding the Coronavirus crisis. With the work to develop social networking activities in general, and the dissemination of social networks for all employees, with the importance of providing them with training on how to deal with social networks. The study found that despite the presence of many positive activities in hospitals, resulting from public relations activities in managing the stages of the Coronavirus pandemic crisis, this reflects to some extent the openness policies that university hospitals have recently initiated, with the fact that some other hospitals are still dependent on the existence of Acting and then following a reaction policy regarding the Coronavirus crisis, which may have actually affected the consistency of public relations functions with the stages of the crisis. What is required is to work on developing policies and plans to confront/reconsider the causes of sub-crises in order to find solutions to them, and to gain the confidence of the internal and external public more in university hospitals, and then the public relations after the occurrence of the crisis will be able to correct the situation, learn, and get out opportunities Especially significant in the field of medical research conducted by professors and the assisting body in medical schools affiliated with university hospitals.